Climate change: crop performances and potential - Ramlan, Mohd Fauzi (Universiti Putra Malaysia Press, 2011)

(untitled)
The effect of climatic change on food crops and other economic value plantation such as oil palm and rubber has received a major concern for many governmental organisations including universities researchers. The rise in CO2 level that comes together with the higher temperature would certainly affect the crop performances. Since many of the crops are categorised under C3 plants, early maturity resulting in lower yield would be expected. In some studies the reduction in yield is due to the photorespiration of these plants. The global climatic change may also be a concern for many countries in the world. A report from ACOP indicated that the top ten countries such as China, USA, EU, Russia and Japan have contributed to more than half of the CO2 emission in the world. Efforts to bring the CO2 under control will only be seen over a long period of time. However, it has been forecasted that developing countries will certainly overtake the developed world for the CO2 emission after 2015. Opening of many new areas for agricultural purposes has contributed to the increase of CO2 for the developing nations. This report covers the growth study and photosynthetic activities on several horticultural crops, forest perennials and rice. Suggestions of the possible responses on the increase of CO2 are also included. In addition, a biological control using other species of bamboo to reduce the domination of buluh semantan under high voltage transmission lines is also included.In the studies regarding growth of forest species meant for domestication purposes, the suitability of Syzygium campanulatumand Hopea odorata for beautification and landscaping plants has shown some potential. However, modifications on such forest species using growth retardants are important. The use of organic fertiliser for an environmental friendly condition is also highlighted.Since it has been a part of the governmental policy for beautifications, the floriculture and ornamental industry has received special attentions. In the production of chrysanthemum, the industry has been trying to formulate nutrient formulation aimed for highlands and lowlands. A similar study has been done in the production of bell pepper in lowland areas. In-depth analyses on plant partitioning and yield components are highlighted.The potential of using microorganism to establish early growth of oil palm seedling has also been included in this lecture series. Such a potential was shown using microbes such as Azospirillum (Strain Sp7 and CCM 3863) in early establishment at nursery stage. These microbes enhanced the root development of the oil palm seedlings. In addition, the possibility to nitrogen fixation in the roots, which is similar to the association of Rhizobium sp. in legumes, is also highlighted.For rice production, the issue of food security against development is being discussed. Water shortages, high temperature from global warming and crop sustainability are some of the key issues for the future of the crop. It is highlighted that water shortage would result in low tiller ability and high weed infestation. Similarly, high temperature at night would result in reduction in yield as the result in the reduction of the fertility rate of female inflorescence. In conclusion, serious considerations should be made on the increase of carbon dioxide and its influence on the growth of many economic crops. Food security should be looked from all angles and a holistic approach towards solving this issue should be addressed.